"The Possibility of Building a Conceptual Framework for Audit Theory and its Reflection on Improving the Practice of the Profession": A Survey Study of the Opinions of a Sample of Academics and Auditors in the Kurdistan Region of Iraq - عباس هومر, یادگار; شاكر سلطان, أياد (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This research aims to shed light on the importance of the conceptual framework for auditing and the failures that the profession faces in the absence of such a framework, as the conceptual framework constitutes the basic pillar for formulating the standards that govern auditors' practices, in addition to the importance of this framework in establishing the foundations of auditing theory. The research relied in achieving its objectives on analyzing the results of the responses of the research sample members consisting of a group of auditors and academics working in institutes and universities in the Kurdistan Region - Iraq, through the questionnaire form that was distributed to the members of the aforementioned sample, and a set of statistical methods were used to test the research hypotheses. The research reached a number of conclusions, including: The conceptual framework is an important reference for advancing the profession, and the lack of this framework at the local environment level makes the established rules and standards inconsistent with the requirements of this environment. In addition, the conceptual framework must be based on a set of objectives and concepts that constitute the basic idea point in building the framework, which represents the first step in establishing the foundations of auditing theory, which is based on a set of assumptions and principles from which standards and practical application tools for practicing the profession can be derived. The most important recommendations of the research are the necessity for professional associations and bodies in the region to play their role in trying to build a conceptual framework for auditing in light of the academic research and studies prepared by international professional associations and organizations, taking into account the variables of the local environment so that the established standards are consistent with the requirements of this environment.